2012
DOI: 10.1080/10408398.2010.499824
|View full text |Cite
|
Sign up to set email alerts
|

Date Fruits (Phoenix dactyliferaLinn): An Emerging Medicinal Food

Abstract: Date palm is one of the oldest trees cultivated by man. In the folk-lore, date fruits have been ascribed to have many medicinal properties when consumed either alone or in combination with other herbs. Although, fruit of the date palm served as the staple food for millions of people around the world for several centuries, studies on the health benefits are inadequate and hardly recognized as a healthy food by the health professionals and the public. In recent years, an explosion of interest in the numerous hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
217
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(225 citation statements)
references
References 117 publications
4
217
0
4
Order By: Relevance
“…Moreover, Bacillus species were also isolated from similarly high osmopressure food items like honey (Iurlina and Fritz 2005). Similarly, Btana has high osmopressure resulting from the high sugar content in dates (Vayalil 2012). Grant (2004) revealed that high-sugar foods (with low aw) are mainly dominated by xerophilic fungi and osmophilic yeasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Bacillus species were also isolated from similarly high osmopressure food items like honey (Iurlina and Fritz 2005). Similarly, Btana has high osmopressure resulting from the high sugar content in dates (Vayalil 2012). Grant (2004) revealed that high-sugar foods (with low aw) are mainly dominated by xerophilic fungi and osmophilic yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing an extraction technique often involves a trade-off between cost (materials and labor), optimal DNA yield, and the removal of substances that could interfere with polymerase chain reaction (PCR) (Sánchez-Hernández and Gaytán-Oyarzún 2006). Like other fruits, the date presents many challenges for DNA extraction due to its complex composition and the presence of a broad range of polysaccharides, carbohydrates, polyphenols, and fibers, and high salt content, which can interfere with enzymatic and chemical reactions during DNA extraction or PCR analysis (Boudries et al 2007;Vayalil 2012). Here, we applied a modified CTAB (cetyltrimethylammonium bromide) protocol to extract bacterial DNA from the Btana product.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins are also derived from HCAs. There are 255 numerous coumarins known in nature, and they are essentially lactones 256 derived from O-hydroxycinnamic acids by cyclisation and ring closure 257 between the o-hydroxy and carboxyl group (Macheix and Fleuriet, 1990 HCAs are present in fruits in combined forms, and only few exceptional 265 situations result in the accumulation of the free form (Tsao, 2010 including date fruit approximating an average of 10 mg / 100 g (Vayalil, 2012). 272…”
Section: Hydroxy Cinnamic Acids (Hca) 252mentioning
confidence: 99%
“…Date flesh is a readily-accessible source of energy because of its high sugar content (70-85% FW) with a significant share of reducing sugars (glucose and fructose) and very small amount of non-reducing sugars (sucrose) (Al-Farsi and Lee, 2008;Rastegar et al, 2012). Dates possess important radical scavenging activity due to the presence of non-enzymatic antioxidants (phenolic, flavonoid and ascorbic acid) and enzymatic antioxidants (catalase, peroxidase and superoxide dismutase), compounds (Biglari et al, 2008;Awad et al, 2011a) known to have health benefits (Vayalil, 2011). Antioxidants are the complex moieties which can quench and neutralize the free radicals and can prevent oxidation of additional molecules and promote health benefits (Mansouri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Chemically date fruit is composed of total sugars, dietary fibers, proteins, vitamins, fat, mineral contents and a very small starch content (Baliga et al, 2011;Vayalil, 2011), each of which may vary, depending on cultivar type, fruit maturation stage, soil type and agronomic practices (Al-Farsi et al, 2007b;Amira et al, 2011). Moreover, some related studies have also been reported on date fruits from Saudi Arabia and the USA (Al-Turki et al, 2010), Oman (Al-Farsi et al, 2005;2007a), Algeria (Mansouri et al, 2005), Iran (Biglari et al, 2008) and Bahrain (Allaith, 2008).…”
Section: Introductionmentioning
confidence: 99%